The power of coalescent methods for inferring recent and ancient gene flow in endangered Bactrian camels - Tianqi Zhu; Zhen Wang; Ziheng Yang (Proceedings of the National Academy of Sciences, 2025)
Genomic sequence data harbor valuable information concerning the history of species divergence and interspecific gene flow and may offer important insights into conservation of endangered species. However, extracting such information from genomic data requires powerful statistical inference methods. A recent analysis of genomic sequence data found little evidence for gene flow from domestic Bactrian camels into the endangered wild Bactrian species. Nevertheless, the methods used to infer gene flow are based on data summaries and lack the power and precision to represent the complex phylogenetic history of the species with gene flow. Here, we apply Bayesian methods to genomic sequence data to test for both recent and ancient gene flow among the three species in the genus Camelus and to estimate the strength and timing of gene flow. We detect a strong signal of gene flow from domestic into wild Bactrian camels, confirming early evidence based on mitochondrial DNA and the Y chromosome. Overall gene flow appears to affect the autosomal genome uniformly, with similar effective rates of gene flow for exonic and noncoding regions. Estimation of species divergence times is seriously affected if gene flow is not accommodated in the analysis. Our results highlight the power of the coalescent model in analysis of genomic data and the utility of the coding as well as noncoding parts of the genome in elucidating the evolutionary history of modern species.